Bimetallic molybdenum tungsten oxynitride: Structure and electrochemical properties - ZHANG, HONGZHOU (My University, 2013)
Mesoporous molybdenum tungsten oxynitride was synthesised by the temperature-programmed reduction of the bimetallic oxide precursor in ammonia and its electrochemical properties were investigated in 1 M H2SO4 aqueous electrolyte. The reaction product is a single-phase material, in which molybdenum and tungsten are distributed throughout the sample, with mesoporous morphology. The maximum of the pore size distribution is located at approximately 4 nm. Nearly rectangular voltammograms with the presence of small redox peaks were detected by cyclic voltammetry measurements in the acidic aqueous electrolyte, indicating properties relevant to electrochemical supercapacitors. The capacitance of 124 F g?1 was measured by galvanostatic charge?discharge and 43% of the initial capacitance can be retained upon the 400-fold increase in the current density from 0.05 to 20 A g?1. The electrochemical properties and the rate capability of the synthesised material are compared with those of monometallic oxynitrides of molybdenum and tungsten. A symmetric cell assembled with molybdenum tungsten oxynitride electrodes is also evaluated.
PUBLISHED
Keywords: Mesoporous molybdenum tungsten oxynitride